FORMULATION AND EVALUATION OF ALOE VERA GEL LIQUID SOAP PREPARATION (Aloe vera L.) WITH VARIOUS VEGETABLE OILS: FORMULASI DAN EVALUASI SEDIAAN SABUN CAIR GEL LIDAH BUAYA (Aloe vera L.) DENGAN VARIASI MINYAK NABATI - Resmila Dewi; Rina Kurniaty; Cut Suraiya Wahyuni Utami; Erda Marniza (ROCE : Jurnal Pertanian Terapan, 2025)
Aloe vera is one of the plants that is very easy to find in Indonesia. This plant is rich in saponins, lignin, vitamins, and enzymes. Liquid soap is made through a saponification reaction of oil reacted with KOH. This study aims to make a liquid soap formulation from Aloe vera gel with three oil variations: sesame, corn, and soybean oil, and their evaluation test. Aloe vera gel is obtained by peeling the skin of Aloe vera leaves and then taking the gel. Furthermore, the aloe vera gel obtained is made in the form of a liquid soap preparation by hot means where the oil is directly reacted with an alkaline solution at a temperature of 50ºC until it gets a soap base. The evaluation of liquid soap includes an organoleptic test, pH, foam height and stability, and viscosity carried out for 28 days of storage time. The results showed that liquid soap preparations made from cream-colored aloe vera gel, in the form of a thick liquid and a distinctive smell from oil, had a pH of 9.4 – 9.7, and the height and stability of the foam at t0 minutes between 30 mm – 93 mm and t5 minutes between 25 mm – 500 mm, viscosity 1133.0 cP – 1133.7 cP. Based on the results of the evaluation test, it can be concluded that liquid soap preparations from Aloe vera gel with three oil variations can produce good liquid soap because it has met the requirements of the organoleptic test, pH, viscosity, and foam height and stability.